Global issues in mediation - Nolan-Haley, Jacqueline M. 1949-; Deason, Ellen E.; Gonstead, Mariana Hernandez-Crespo (West Academic Publishing, 2019)
Mediation overview --Court-connected and mandatory forms of mediation --The role of culture in international mediation --Legal issues and regulation of mediation --Ethical challenges --Combining mediation with other ADR processes --International mediation in the context of investor-state disputes --Peacemaking mediation --Case studies
Includes bibliographical references and index
Keywords: Dispute resolution (Law); Mediation